Single-Objective Optimization of a CMOS VCO Considering PVT and Monte Carlo Simulations - Castañeda-Aviña, Perla Rubi; Tlelo-Cuautle, Esteban; de la Fraga, Luis Gerardo (Mathematical and computational applications, 2020)
The optimization of analog integrated circuits requires to take into account a number of considerations and trade-offs that are specific to each circuit, meaning that each case of design may be subject to different constraints to accomplish target specifications. This paper shows the single-objective optimization of a complementary metal-oxide-semiconductor (CMOS) four-stage voltage-controlled oscillator (VCO) to maximize the oscillation frequency. The stages are designed by using CMOS current-mode logic or differential pairs and are connected in a ring structure. The optimization is performed by applying differential evolution (DE) algorithm, in which the design variables are the control voltage and the transistors’ widths and lengths. The objective is maximizing the oscillation frequency under the constraints so that the CMOS VCO be robust to Monte Carlo simulations and to process-voltage-temperature (PVT) variations. The optimization results show that DE provides feasible solutions oscillating at 5 GHz with a wide control voltage range and robust to both Monte Carlo and PVT analyses.